Improved Understanding of the Role of Gene and Genome Duplications in Chordate Evolution With New Genome and Transcriptome Sequences - Aase-Remedios, Madeleine E.; Ferrier, David E. K. (Frontiers in Ecology and Evolution, 2021)
Comparative approaches to understanding chordate genomes have uncovered a significant role for gene duplications, including whole genome duplications, giving rise to and expanding gene families. In developmental biology, gene families created and expanded by both tandem and whole genome duplications (WGDs) are paramount. These genes, often involved in transcription and signalling, are candidates for underpinning major evolutionary transitions because they are particularly prone to retention and subfunctionalisation, neofunctionalisation, or specialisation following duplication. Under the subfunctionalisation model, duplication lays the foundation for the diversification of paralogues, especially in the context of gene regulation. Tandemly duplicated paralogues reside in the same regulatory environment, which may constrain them and result in a gene cluster with closely linked but subtly different expression patterns and functions. Ohnologues (WGD paralogues) often diversify by partitioning their expression domains between retained paralogues, amidst the many changes in the genome during rediploidisation, including chromosomal rearrangements and extensive gene losses. The patterns of these retentions and losses is still not fully understood, nor is the full extent of the impact of gene duplication on chordate evolution. The growing number of sequencing projects, genomic resources, transcriptomics, and improvements to genome assemblies for diverse chordates from non-model and under-sampled lineages like the coelacanth, as well as key lineages, such as amphioxus and lamprey, has allowed more informative comparisons within developmental gene families as well as revealing the extent of conserved synteny across whole genomes. This influx of data provides the tools necessary for phylogenetically-informed comparative genomics, which will bring us closer to understanding the evolution of chordate body plan diversity and the changes underpinning the origin and diversification of vertebrates.